Impact of a Training Programme on the Empathy Skills of Nursing Students During the COVID‐19 Pandemic: A Quasi‐Experimental Study - Maryam Sedaghati Kesbakhi; Simin Arab; Leila Hosseini Tabaghdehi; Camelia Rohani (Nursing Open, 2025)
ABSTRACT Aim To explore the impact of an innovative empathy training programme on undergraduate nursing students' empathy skills in the course of developing the COVID‐19 pandemic. Design A quasi‐experimental study with one group and a pretest–posttest design. Methods The training programme was produced with inspiration from an earlier qualitative study. It was held as an online 2‐hour daily programme during 5 continuous weeks for 71 nursing students in the fourth, sixth and eighth semesters. Data collection was done before (T1), immediately (T2) and 2 months (T3) after the training programme using the Jefferson Scale of Empathy–Nursing Student version R. The data were analysed using the repeated measures analysis of variance (ANOVA). Results The mean scores of total empathy scale (T1:108.1 ± 0.06 to T3: 118.6 ± 0.4) and its three subscales (perspective taking; T1: 56.2 ± 0.9 to T3: 60.5 ± 2.5, compassionate care; T1: 43.1 ± 0.1 to T3: 46.5 ± 0.9, and standing in the patient's shoes; T1: 8.7 ± 0.5 to T3: 12.2 ± 0.6) increased over time. These results showed that our two hypotheses were accepted (p < 0.0001) and the training programme had a moderately positive effect on increasing students' empathy scores (effect size: 0.53–0.69), except for the compassionate care subscale, which only showed a small positive effect (effect size: 0.31). However, the mean score of empathy in female students was significantly higher than in males at T1 (p < 0.01), there was no difference between male and female students at T3 (p > 0.05). Conclusions This training programme can be incorporated into the undergraduate nursing curriculum planning to improve the quality of care and the relationship between patients and nursing students in clinical settings. Implications for the Profession and/or Patient Care Empathy is one of the essential nursing professional skills. Teaching this skill can be useful in increasing patients' quality of care.